Robust growth in Central Asia 2019-24: In the face of uncertainties, the pandemic and protracted war in the neighborhood - Stephan Barisitz (Oesterreichische Nationalbank (OeNB), 2025)
In contrast to most Central, Eastern and Southeastern European (CESEE) economies, Central Asia (CA) - comprising Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan - has witnessed quite robust demographic as well as economic growth in the period from 2019 to 2024. This period was marked by the aftermath of the oil price and Russian ruble plunge of 2014-16, the COVID-19 crisis (2020-21) and Russia's invasion of Ukraine and incisive Western sanctions imposed on Russia (2022-24). China overtook Russia to become the region's most important trading partner, while trade shares of EU countries have somewhat declined. Led by Kazakhstan (2015), most Central Asian countries made steps to move away from their US dollar pegs toward inflation targeting. Higher energy and commodity prices, Russia's surprisingly swift recovery from its Western sanctions-induced recession following its invasion of Ukraine, inflows of some highly skilled migrants from Russia ("relokanty"), strongly growing labor migration to and remittance inflows from Russia, and increased gains from transit trade with the region's northern neighbor all underpinned CA's economic expansion in 2022, 2023 and 2024. There are strong indications that at least part of CA's recently swelling transit trade has been in circumvention of Western sanctions against Russia. In the long run, Russia's war in Ukraine and heightened tensions between the United States and China could deepen global economic fragmentation, yet losses for CA according to IMF experts would likely remain comparatively limited given the region's already high level of trade concentration with its immediate neighbors China and Russia.
Keywords: E52; E63; G21; G28; P34; 330; state-led economy; structural reforms; heterogeneity; monetary policy; exchange rate regime; sanctions; banking; oil and gas exporters; relokanty; remittances; transit trade; COVID-19; fragmentation; Central Asia; Kazakhstan; Kyrgyzstan; Tajikistan; Turkmenistan; Uzbekistan